PORTRAYAL OF DISMENORRHEA BASED ON MENARCHE AGE, STRESS, AND EATING CONSUMPTION OF STUDENTS IN SCHOOL OF HEALTH AND LIFE SCIENCES: A CROSS-SECTIONAL STUDY - Mifaidah Kusumawati; Syahrul Ramadhan; Ayik Mirayanti Mandagi; Mohammad Zainal Fatah (Lembaga Penelitian dan Terapan untuk Kesehatan Jiwa (Lenterakaji), 2023)
Background: Factors that can influence of dysmenorrhea are menarche age, stress, consuming fast food, alcohol, and smoking. Purpose: Analysing the strong relationship between the incidence of primary dysmenorrhea and menarche age, stress, and food consumption of School of Health and Life Sciences, Universitas Airlangga students. Methods: This is cross-sectional study of 51 respondents with independent variables menarche age, stress level, and food consumption pattern, and dependent variable was primary dysmenorrhea. Data analysis used a statistical test the strength of the relationship by looking at the contingency coefficient (c). Results: Most of the female students experienced dysmenorrhea in the mild and moderate pain category was 23 people (43.4%), menarche age of 11-13 years was 45 people (84.9%), normal stress was 17 people (32.1%), unhealthy eating patterns was 31 people (58.5%). There was a weak relationship between menarche age and primary dysmenorrhea (c=0.105), a moderate relationship between stress and primary dysmenorrhea (c=0.495) and a weak relationship between food consumption patterns and primary dysmenorrhea (c=0.347). Conclusion: Female students had primary dysmenorrhea in the mild and moderate pain categories, stress levels were in the normal category, and food consumption patterns were in the poor category. The most related factor was the stress factor. Abstrak Latar Belakang: Faktor-faktor yang dapat memengaruhi terjadinya dismenorea antara lain usia menarche, stres, mengonsumsi makanan cepat saji, mengonsumsi alkohol, dan merokok. Tujuan: Menganalisis kuat hubungan kejadian faktor dismenorea primer dengan usia menarche, stres, dan konsumsi makan mahasiswi Sekolah Ilmu Kesehatan dan Ilmu Alam Universitas Airlangga. Metode: Ini adalah studi cross-sectional pada 51 responden dengan variabel independen yaitu usia menarche, tingkat stres, dan pola konsumsi makanan, dan variabel dependen yaitu dismenorea primer. Analisis data menggunakan uji statistik kuat hubungan dengan melihat koefisien kontingensi (c). Hasil: Mayoritas mahasiswi mengalami dismenorea pada kategori nyeri ringan dan sedang sebanyak 23 (43,4%), usia menarche 11-13 tahun sebanyak 45 (84,9%), stres normal sebanyak 17 (32,1%), pola konsumsi makan tidak baik sebanyak 31 (58,5%). Terdapat hubungan lemah usia menarche dengan dismenorea primer (c=0,105), hubungan yang sedang tingkat stress dengan dismenorea primer (c=0,495) dan hubungan lemah pola konsumsi makan dengan dismenorea primer (c=0,347). Kesimpulan: Mahasiswi memiliki dismenorea primer pada kategori nyeri ringan dan sedang, tingkat stres terdapat pada kategori normal, pola konsumsi makan pada kategori tidak baik. Faktor yang paling berhubungan yaitu faktor stress.